Semiconducting two-dimensional nanomaterials for optoelectronic devices - Pak, S (2018)
The emergence of transition metal dichalcogenides (TMDCs) monolayers which exhibit a variety of structural and electronic configurations has attracted significant attention as the monolayers have been found to possess unique characteristics that are not observed in their bulk forms. These materials have sufficiently wide electronic bandgaps (Eg = 1~2 eV) with a direct band gap nature, which makes them suitable for electronic and optoelectronic applications. Their atomically-thin configuration coupled with the presence of covalent bonds between the transition metal atoms and the chalcogenide atoms ensure that the materials are highly flexible and transparent. As a result, TMDC monolayers have potential in applications such as flexible and transparent optoelectronic devices. In this thesis, TMDC monolayers are studied ranging from the synthesis of these materials to their implementation in optoelectronic device applications. The aim of this research is to enhance our understanding of the electronic and optoelectronic behaviour of these layers and to demonstrate the feasibility of using TMDC monolayers in next-generation device applications. The initial goal is to synthesise large-sized single crystals using chemical vapour deposition, where the nucleation density can be controlled through solution-processing and the loading of an extremely small amount (0.01 mg) of transition metal oxide precursors. It is shown that the nucleation density can be dramatically decreased so that large grain sizes up to 500 μm can be obtained in the TMDC monolayer film. Using this approach, the synthesis of MoS2/WS2 heterostructures is shown to be possible using a one-step process, which results in a clean interface without much mixing of the precursors. Following a discussion of the synthesis process, my DPhil thesis then focuses on chemical doping of the surface of the monolayers and the role of strain engineering on the tuning of the physical, optical, and electrical properties of the TMDC monolayers. It was found that the carrier density of an MoS2 monolayer could be modulated and that properties such as the photoresponsivity, detectivity, and photoresponse time can be controlled through changes to the energy band structure. Also, strain engineering of TMDC monolayers and hetero-bilayers is successfully demonstrated. The excitonic behaviour of an MoS2/WS2 hetero-bilayer, when subjected to a small mechanical strain (up to 0.7 %), is experimentally observed for the first time, and the effect of interlayer coupling on the wavelength of the photoluminescence peak as well as changes in the photoluminescence intensity are demonstrated. Lastly, the thesis considers specific optoelectronic applications of TMDC monolayers. These optoelectronics applications include: a (1) 2D/QD vertical heterojunction phototransistor with an enhanced photoresponse time of 950 μs and photoresponsivity of 6120 A/W and a (2) two-terminal MoS2 flexible photodetector with surface functionalisation that decreases the response time to 0.7 s. The results and performance of the materials and devices presented in this thesis show particular promise for next-generation, flexible and transparent device applications.